Lithuania’s Response to the Crisis of Irregular Migration in 2021–2024 - Bartasevičius, Vainius; Fuks, Vytenis; Nakrošis, Vitalis (Politologija, 2025)
A detailed analysis of Lithuania’s operational and strategic responses to irregular migration flows from Belarus has been lacking. The ongoing attempts to cross the EU external border, facilitated by Belarusian authorities, started in the summer of 2021, and coincided with simultaneous crisis situations, namely, the difficulties associated with the implementation of international/EU economic sanctions against Russia and Belarus and high energy prices. Drawing on extensive desk research and five semi-structured interviews with Lithuanian policy officials, the study analyses the institutional changes related to the management of the crisis, as well as long-term policy decisions in the field of migration management. We have found that, at the operational level, the interconnected nature of crises compelled public authorities to enhance inter-institutional cooperation and strengthen crisis coordination mechanisms. At the strategic level, Lithuania focused its efforts on strengthening its border with Belarus, and advocating the adaptation of EU migration legislation to situations of ‘migrant instrumentalisation’.
Keywords: polycrisis; governance capacity; crisis coordination; operational response; strategic decisions; Lithuania